The Role of Civil Servant Investigators (PPNS) in Implementing Regulation of the Director General of Sea Transportation No: Kp.222/Djpl/2019 in Supporting the Main Duties and Functions of Class II Bitung Sea and Coast Guard Bases for Enforcement of Law No. 17 of 2008 Concerning Shipping - Suhana, Iwan; Bogar, Wilson; Mandagi, Marthinus (Technium Social Sciences Journal, 2023)
This study aimed to 1) find out how the Role of Civil Servant Investigators (PPNS) in the Implementation of the Director General of Sea Transportation Regulations No: Pk.222/DJPL/2019 in supporting the main tasks and functions of Class II Bitung Sea and Coast Guard Unit Base for Law Enforcement - Invite No. 17 of 2008 concerning shipping; 2) find out the factors that determine the Civil Servant Investigator (PPNS) in the Implementation of the Director General of Sea Transportation Regulation No: Pk.222/DJPL/2019 in supporting the main tasks and functions of Bitung Class II Sea and Coast Guard Unit Base for Enforcement of Laws No. 17 of 2008 concerning shipping. This study used a qualitative research method with purposive sampling. Sources of research data are informants, observations and documents. Data analysis techniques namely reduction, data presentation and conclusion. The research location is the Class II Coastal Marine Guard Base Office, Bitung City. The results of the study show that not all Civil Servant Investigators understand their main duties and functions so that the application of the Director General of Sea Transportation Regulation No: KP.222/DJPL/2019 in Supporting the Main Duties and Functions of Class II Bitung Coastal Sea Guard Base for Enforcement of Law no. 17 of 2008 concerning Shipping is not yet optimal. Factors that influence it are communication, resources, weather, responsibility and morale, as well as the mental and infrastructure of the ship as a support.